Effects of different surfaces in time-motion characteristics in youth elite tennis players - Gale-Ansodi, C.; Castellano, J.; Usabiaga, O. (International Journal of Performance Analysis in Sport, 2016)
The aim of this study was to compare the physical profile between clay and hard court in match-play for high-level young tennis players using GPS technology. 4 female and 10 male high-level young Spanish tennis players (under 12 years n=28 and under 14 years n=28 records) took part in the study (age 12.9 ±1.3 years). Eleven portable GPS devices (MinimaxXv.4.0, Catapult Innovations) operating at a sampling frequency of 10 Hz were used to collect data. Physical demands were assessed over 42 tennis matches, with individual players being tracked in 2 matches on hard and 2 matches on clay court (4 matches by player) totalling 56 individual recordings on two surfaces: CLAY court (n=28) and HARD court (n=28). The results showed significant differences between surfaces (HARD>CLAY) in acceleration distance covered (DCAm) HARD= 42.4±5.7 vs. CLAY= 31.6±8.9 in m·min-1; F(3, 56)= 20.6; p= 2 p= 0.30; ES=0.59), average speed (HARD= 3.2±0.4 vs. CLAY= 2.8±0.6 in m·s-1; F(3, 56)= 3.7; p= 0.061; 2 p =0.07; ES=0.48) and maximum speed (HARD= 4.6±0.6 vs. CLAY= 4.0±0.7 in m·s-1; F(3, 56)= 5.9; p= 0.019; 2 p= 0.11; ES=0.60). The main conclusion of this study was the hard court games were characterized by high intensity efforts. Tennis players who played matches on hard court covered a greater distance accelerating, with more pacing and higher speeds. The data suggests that coaches should adapt the training strategy to the type of surface on which the players will play their next tournament, in order to improve performance and/or propose protocols to prevent injuries.